METAL CORROSION EFFECT OF 1,2-DIBROMO-TETRAFLUOROETHANE IN AQUEOUS SOLUTION – STAINLESS STEEL INOXSUS 304 CORROSION - Tuấn (Journal of Military Science and Technology, 2021)
Report on research center, surveying the impact of Khladon-114B2.VN (1,2-dibromo tetrafluoroethane) on unchanged materials - Mainly materials for manufacturing military aircraft fire suppression systems the. Research results, check quality format Khladon-114B2.VN do Research group are not give up the amation to the system of the fire system. Survey results show that, Khladon-114B2.VN does not cause corrosion for stainless steel materials, stainless steel corrosion rate of Khladon-114B2.VN calculated by Taflen method is about 0.0042mm / year.